New Routing Protocol LISP Splits Identification and Location - Pham, Duy Loc (Trường Đại học Đà Lạt, 2012)
At the moment, IP Address is both identification and location of a host in the Internet. Because this limitation, we have some difficulties when a host is downloading roamed to other locations. LISP (Locator Identifier Separation Protocol) protocol was introduced to solve this problem, beside that LISP also resolved the problem of exhaustion IPv4 addresses without changed the current architect of IPv4 address. Up to now, LISP has been still a draft version and it has been developing to be a new complete routing protocol.